Association of age at first calving with longevity, milk yield, and fertility up to the third lactation in a herd of Holstein dairy cows in Japan - Hiromi KUSAKA; Takeshi YAMAZAKI; Minoru SAKAGUCHI (The Society for Reproduction and Development, 2023)
Accelerating age at first calving (AFC) is a strategy for sustainable dairy farming, whereas the impact of a reduction in AFC on long-term performance remains unclear. In this study, longevity and milk productivity until the end of the third lactation period were investigated retrospectively according to AFC. A total of 169 cows were categorized according to AFC as young, moderate, old, and very old (< 22.5, 22.5 -< 24.0, 24.0 -< 25.5, and > 25.5 months). The young AFC group had approximately 70 kg lower body weight before first calving (620 vs. 695 kg, P < 0.05) and experienced their first calving approximately 4.2 months earlier than the very old AFC group (21.9 vs. 26.1 months, P < 0.05). The survival rate at the third calving stage was 61% in the young AFC group, which was higher than those in the moderate (42%), old (35%), and very old (33%) AFC groups. In the young AFC group, no cows were culled because of low productivity and hoof disease, compared to 5.0-8.1% of older AFC cows. The young AFC group had a higher overall lifetime milk yield (cumulative milk yield/days from birth to the end of final lactation) than the old AFC group (14.3 vs. 8.7 kg/d, P = 0.11). The cows that survived the third calving had better reproductive performance than non-surviving cows; however, no statistical difference was detected among the AFC groups. In conclusion, AFC as early as 22.5 months could be associated with better survivability and higher overall lifetime milk yield than older AFC without impairing reproductive performance. Our results suggest that accelerating AFC may lead to higher profitability.